Facile synthesis of a porous polynorbornene with an azobenzene subunit: selective adsorption of 4-nitrophenol over 4-aminophenol in water. Issue 40 (7th October 2020) - Peng, Shan-Qing; Zhang, Butian; Fan, Wenhao; Wang, Shuifeng; Zhang, Zhi-Hao; Liu, Yan; Chen, Shi-Lu; Huang, Mu-Hua
Abstract : The azo-linked porous polynorbornene was synthesized via the robust reductive azo-coupling and Ring-Opening-Metathesis-Polymerization (ROMP) polymerization, which selectively adsorbed 4-nitrophenol over 4-aminophenol in water. Abstract : This paper reports the design and facile synthesis of porous polynorbornenes containing a 4, 4′-dialkoxy-azobenzene subunit (named Azo-POP-13 and Azo-POP-14). They were synthesized by the robust reductive azo-coupling polymerization of the Ring-Opening-Metathesis-Polymerization (ROMP) product on bis- para -nitrophenylether of the norbornene diol. The polymerization rate of exo -NBNPE ( k app = 18.7 × 10 −2 s −1 ) is faster than that of endo -NBNPE ( k app = 3.64 × 10 −2 s −1 ). The as-synthesized Azo-POP-13 was found to selectively adsorb 4-nitrophenol (4-NP) over 4-aminophenol (4-AP) in water, with a selectivity up to 14.6 and good recyclability.